Insights into aerosol chemical composition and optical properties at Lulin Atmospheric Background Station (2862 m asl) during two contrasting seasons - Shantanu Kumar Pani; Lin, Neng-Huei; Lee, Chung-Te; Stephen M. Griffith; Chang, Jackson Hian Wui; Hsu, Bo-Jun (Elsevier BV, 2022)
Continental outflows from peninsular Southeast Asia and East Asia dominate the widespread dispersal of air pollutants over subtropical western North Pacific during spring and autumn, respectively. This study analyses the chemical composition and optical properties of PM₁₀ aerosols during autumn and spring at a representative high-altitude site, viz., Lulin Atmospheric Background Station (23.47°N, 120.87°E; 2862 m a.s.l.), Taiwan. PM₁₀ mass was reconstructed and the contributions of major chemical components were also delineated. Aerosol scattering (σsp) and absorption (σap) coefficients were regressed on mass densities of major chemical components by assuming external mixing between them, and the site-specific mass scattering efficiency (MSE) and mass absorption efficiency (MAE) of individual components for dry conditions were determined. NH₄NO₃ exhibited the highest MSE among all components during both seasons (8.40 and 12.58 m2 g−1 at 550 nm in autumn and spring, respectively). (NH₄) ₂SO₄ and organic matter (OM) accounted for the highest σsp during autumn (51%) and spring (50%), respectively. Mean MAE (mean contribution to σap) of elemental carbon (EC) at 550 nm was 2.51 m² g-¹ (36%) and 7.30 m² g-¹ (61%) in autumn and spring, respectively. Likewise, the mean MAE (mean contribution to σap) of organic carbon (OC) at 550 nm was 0.84 m² g-¹ (64%) and 0.83 m2 g-¹ (39%) in autumn and spring, respectively. However, a classification matrix, based on scattering Ångström exponent, absorption Ångström exponent, and single scattering albedo (ω), demonstrated that the composite absorbing aerosols were EC-dominated (with weak absorption; ω = 0.91–0.95) in autumn and a combination of ECdominated and EC/OC mixture (with moderate absorption; ω = 0.85–0.92) in spring. This study demonstrates a strong link between chemical composition and optical properties of aerosol and provides essential information for model simulations to assess the imbalance in regional radiation budget with better accuracy over the western North Pacific.